Pengujian Pecking Order Pada Perusahaan Perkebunan Di Indonesia - Munawar, Aang; Sanim, Bunasor; Manurung, Adler Hayman; Achsani, Noer Azam (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
This research examines capital structures or financial policy in Indonesia plantation firms with pecking order theory. Plantation firm was classified on status (listed and unlisted) and product (palm oil and non palm oil). Panel data methodology is used to test the empirical hypotheses over a sample of 22 Indonesia plantation firms during seven years period 2002 â 2008. The result of this research shows there is a significant cash deficit and product variables positively influence to increase long term debt. This evidence shows that pecking order theory used on financial policy and palm oil firms have cash deficit and long term debt more than non palm oil firms. In accordance to T test, there is a significant difference cash deficit and long term debt on firm status but long term debt only a significant difference on product firm.